2009
DOI: 10.1038/msb.2009.52
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis reveals a tight link between transcription factor dynamics and regulatory network architecture

Abstract: Although several studies have provided important insights into the general principles of biological networks, the link between network organization and the genome-scale dynamics of the underlying entities (genes, mRNAs, and proteins) and its role in systems behavior remain unclear. Here we show that transcription factor (TF) dynamics and regulatory network organization are tightly linked. By classifying TFs in the yeast regulatory network into three hierarchical layers (top, core, and bottom) and integrating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
210
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(234 citation statements)
references
References 85 publications
18
210
0
Order By: Relevance
“…Using a vertex-sort algorithm 19 we determined the number of levels in the Top-down and Bottomup hierarchical decomposition of the TRNs of B. subtilis and E. coli (see Methods). The number of levels was found to be smaller than that observed in randomized networks (Table S1).…”
Section: Hierarchical Organization Of Transcriptional Regulatory Netwmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a vertex-sort algorithm 19 we determined the number of levels in the Top-down and Bottomup hierarchical decomposition of the TRNs of B. subtilis and E. coli (see Methods). The number of levels was found to be smaller than that observed in randomized networks (Table S1).…”
Section: Hierarchical Organization Of Transcriptional Regulatory Netwmentioning
confidence: 99%
“…Leaf-removal procedure within the vertex-sort algorithm 19,42 can be used to decompose nodes into different levels in two different ways: Top-down and Bottom-up hierarchy. We determined the number of actual levels in both the Top-down and Bottom-up hierarchal decompositions of the TRNs of B. subtilis and E. coli (Table S1).…”
Section: Hierarchical Decomposition Of Transcriptional Regulatory Netmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth and development in multicellular organisms are regulated at many levels by transacting molecules following well-structured regulatory hierarchies (Riechmann et al, 2000;Davidson, 2001;Wray et al, 2003;Jothi et al, 2009). Understanding the regulatory hierarchy of wood formation will offer novel and more precise genetic approaches to improve the productivity of forest trees.…”
Section: Introductionmentioning
confidence: 99%
“…Luscombe et al (2004) have shown that gene regulation in response to exogenous stimuli tends to involve fewer TFs per target and shorter regulatory cascades than do endogenous regulatory controls (such as the cell cycle). Additionally, Jothi et al (2009) found that differences in TF half-life were associated with a TF's position in the hierarchically organized regulatory network, such that TFs associated with environmental stimuli tended to be long-lived, while those TFs involved in computing the appropriate response to those stimuli had shorter half-lives.…”
Section: Introductionmentioning
confidence: 99%